Młodopolski romans popularny - kłopoty z teorią - Pochłódka, Anna (Wydawnictwo Naukowe UAM, 2008)
This article offers an outline of the history of theoretical interest in popular literature, in particular - romance. The author discusses mainly the research propositions developed on Polish grounds, starting with the differentiation of elite or 'highly artistic' literature and the popular one. Following Jacek Kolbuszewski, the author proposes to determine the range of popular literature on cultural instead of sociological basis. Also Anna Martuszewska's notion is supported, who claims that popularity is an immanent feature of this kind of literature. The question of probability in the Young Poland romance is considered as well. The methodological ideas are illustrated by references to specific novels. Popular fiction is multiform and set in the artistic, historical and sociological context. Relating to the presented material, the author proposes a thesis that in the period of Young Poland two currents of romantic fiction coexisted: the 'tendentious-fabulous' (represented by Anna Karwatowa nee Bardzka, Natalia Bardzka, Wanda Grot-Bęczkowska, Helena Mniszkówna) and the 'naturalistic' one (represented by Mikołaj Czerny, Marian Cawalewicz, Mieczysław Srokowski, Kazimierz Przerwa Tetmajer). It is determined upon the inherent characteristics of particular texts (i.e. style, construction of hero, manner of creation of the presented world, etc.) which current a novel represents.
The popular romance of Young Poland - trouble with the theory